Efeito da aplicação foliar de silício em rúcula cultivada em dois tipos de solos - Gerrero, Amaralina Celoto [UNESP]; Borges, Luciana da Silva [UNESP]; Fernandes, Dirceu Maximino [UNESP] (Universidade Federal de Uberlândia (UFU), 2011)
The rocket is a leafy herbaceous annual, features small size, rapid vegetative growth and short life cycle. Silicon is considered a beneficial element, and despite not having his definition of essential mineral nutrition of plants has been widely used in research. The objective was to assess the effect of foliar fertilization with silicon levels in soils in the cultivation of the rocket. The experiment was conducted in a greenhouse in the DRN / Soil Science, UNESP / FCA, Botucatu-SP, from April 15 to May 20, 2008. The experimental design was randomized blocks in factorial 2x5 (two solos and five doses of silicon). At the end of the experiment, evaluated at the point of harvest to plant height (cm), leaf area (LA), total fresh mass (TFM), total dry matter (TDM), leaf area ratio (LAR), specific weight Leaf (PEF), amount of water in the shoot (AWS) and content and accumulation of silicon in the leaves. It was concluded that silicon had no influence on the agronomic characteristics of the rocket and changes were only to soil type.
Effect of foliar application of silicon in rocket grown in two types of soil
Keywords: Eruca sativa Mill; Silicon; Plants mineral nutrition; Analysis of growth